On Life and Death: The Intertwined Relationship Between History and Modernist English Literature - Ava Kostka (The Toro Historical Review, 2024)
Virginia Woolf's novel Mrs. Dalloway (1925) is used as an example of English Modernist prose to evaluate the ways in which the period's historical context affected the literature that arose from the movement, particularly relating to themes of life and death, while recognizing the the literature itself influenced the history it created in turn.